1998
DOI: 10.1046/j.1365-8711.1998.01468.x
|View full text |Cite
|
Sign up to set email alerts
|

Positions of hydroxyl masers at 1665 and 1667 MHz

Abstract: The Australia Telescope Compact Array has been used to observe more than 200 1665‐MHz hydroxyl masers south of declination −16° and derive their positions with typical rms uncertainties of 0.4 arcsec. Many of the 1665‐MHz maser sites are found to have 1667‐MHz OH maser counterparts which are coincident, within the errors. The resulting position list presented here includes all well‐documented, previously reported 1665‐MHz masers close to the Galactic plane in the galactic longitude range 230° (through 360°) to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

38
467
5

Year Published

2002
2002
2022
2022

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 202 publications
(510 citation statements)
references
References 13 publications
38
467
5
Order By: Relevance
“…Like these rarer types of methanol masers, excited-state OH masers are more likely to be found towards sources showing 12.2-GHz masers, meaning that they are detected towards a subset of the more evolved 6.7-GHz methanol masers, but their occurrence is not as closely linked to the 6.7-and 12.2-GHz methanol maser luminosities. This result is also reflected in a comparison between the occurrence of 1665-and 1667-MH OH masers (Caswell 1998) with 6.7-and 12.2-GHz methanol maser sources .…”
Section: Associations With Excited-state Oh Masersmentioning
confidence: 75%
“…Like these rarer types of methanol masers, excited-state OH masers are more likely to be found towards sources showing 12.2-GHz masers, meaning that they are detected towards a subset of the more evolved 6.7-GHz methanol masers, but their occurrence is not as closely linked to the 6.7-and 12.2-GHz methanol maser luminosities. This result is also reflected in a comparison between the occurrence of 1665-and 1667-MH OH masers (Caswell 1998) with 6.7-and 12.2-GHz methanol maser sources .…”
Section: Associations With Excited-state Oh Masersmentioning
confidence: 75%
“…Column 15 of Table 1 lists the associations with 12.2-GHz methanol and OH masers from Breen et al (2012); Caswell (1998) and Caswell et al (2013). Note that the 12.2-GHz associations are complete, coming from targeted observations towards the MMB sources.…”
Section: Resultsmentioning
confidence: 99%
“…From observations with the VLT MIR VISIR camera, Grave et al (2014) found indications that this region consists of two main luminous sources (O4V and O5V) which account for at least half of the luminosity from this region. As well as being proximate to the Hii region G333.6-0.22, this molecular outflow source is also associated with MSX and 1.2-mm dust sources (Mookerjea et al 2004) and masers of H 2 O and OH (Batchelor et al 1980;Caswell 1998).…”
Section: G333 Outflow/infall Sourcesmentioning
confidence: 88%
“…The Mopra beam is 36 arcseconds at 3-mm wavelengths. The references are: (a) Mookerjea et al (2004); (b) Becklin et al (1973); (c) Murphy et al (2010); (d) Figuerêdo et al (2005); (e) Breen et al (2007); (f) Caswell (1998); (g) Caswell et al (1995). Ladd et al (2005) and the beam efficiencies used are as listed there.…”
Section: Observations and Data Reductionmentioning
confidence: 99%